2018
DOI: 10.3389/fpsyg.2018.01082
|View full text |Cite
|
Sign up to set email alerts
|

Angels and Demons: The Effect of Ethical Leadership on Machiavellian Employees’ Work Behaviors

Abstract: Machiavellians can be characterized as goal-driven people who are willing to use all possible means to achieve their ends, and employees scoring high on Machiavellianism are thus predisposed to engage in unethical and organizationally undesirable behaviors. We propose that leadership can help to manage such employees in a way that reduces undesirable and increases desirable behaviors. Studies on the effects of leadership styles on Machiavellian employees are scarce. Here we investigate the relationship of ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 63 publications
2
65
2
4
Order By: Relevance
“…Accordingly, high-Machs do not always engage in unethical behavior, but only when they feel that it is a way to achieve their goals (Kuyumcu and Dahling, 2014). Under some circumstances, Machiavellianism can even be positive for organizations because Machs may find it serves them to adapt their behavior in such a way that it benefits the organization (Belschak et al, 2015(Belschak et al, , 2018. For instance, high-Machs have been shown to engage in more citizenship behaviors when having a transformational leader (Belschak et al, 2015) and to show better task performance when faced with inadequate resources (Kuyumcu and Dahling, 2014).…”
Section: The Moderating Role Of Machiavellianismmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, high-Machs do not always engage in unethical behavior, but only when they feel that it is a way to achieve their goals (Kuyumcu and Dahling, 2014). Under some circumstances, Machiavellianism can even be positive for organizations because Machs may find it serves them to adapt their behavior in such a way that it benefits the organization (Belschak et al, 2015(Belschak et al, , 2018. For instance, high-Machs have been shown to engage in more citizenship behaviors when having a transformational leader (Belschak et al, 2015) and to show better task performance when faced with inadequate resources (Kuyumcu and Dahling, 2014).…”
Section: The Moderating Role Of Machiavellianismmentioning
confidence: 99%
“…Moreover, our findings show that ethical leaders can create a context in which people intuitively refrain from choosing unethical behavior in corruption-related dilemmas and thereby hopefully change the engagement in corrupt behavior, especially for employees whose intuition would promote such behavior, such as employees with high-Mach. Previous work (Belschak et al, 2018;Ruiz-Palomino and Linuesa-Langreo, 2018) suggested that by applying ethical leadership, leaders could bring high-Machs to reduce their tendencies to engage in unethical behavior. However, our experimental results of Study 2 indicate that ethical leadership was marginally more efficient in reducing unethical tendencies in low-Machs than in high-Machs.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although recent researches have indicated that ethical leadership can influence subordinates' work-related behaviors (Garba et al, 2017;Walumbwa et al, 2017;Belschak et al, 2018), we still do not know whether subordinates with different cultural values react to ethical leaderships differently (Zhu et al, 2015). Brown and Mitchell (2010) have shown that differences in subordinates' cultural values (such as power distance) could influence the effect of ethical leadership on subordinates' workrelated outcomes.…”
Section: Introductionmentioning
confidence: 99%